2019
DOI: 10.1108/ijhg-05-2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of Arabic YouTube videos for cancer treatment

Abstract: Purpose The purpose of this paper is to describe and assess Arabic videos related to cancer treatment to gain insights about the nature of health information as it is shared on YouTube. Accordingly, future strategies for different bodies are suggested to promote effective communication. Design/methodology/approach The approach is to select a representative sample of YouTube videos for certain search terms related to cancer treatment in the Arabic language. In order to identify the search terms, Google Trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The first YouTube video study for assessing the quality and reliability of medical information was conducted by Keelan et al (10). Several other studies that followed also showed consistently lower reliability and quality of medical videos (5,(11)(12)(13)(14). Videos produced by academic institutions discussing specific procedures, perioperative care instructions, risks/benefits, and those focusing on actual patient scenarios were deemed the highest in quality and reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The first YouTube video study for assessing the quality and reliability of medical information was conducted by Keelan et al (10). Several other studies that followed also showed consistently lower reliability and quality of medical videos (5,(11)(12)(13)(14). Videos produced by academic institutions discussing specific procedures, perioperative care instructions, risks/benefits, and those focusing on actual patient scenarios were deemed the highest in quality and reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Arabic Internet for cancer-related information can be problematic because much of it is unaccredited or unvalidated by specialists [ 7 , 8 ]. Health information is increasingly being searched for on mobile devices and social media [ 9 ] Misinformation resulting from patients’ increased uploading of cancer data to social media, blogs, and networks raises doubts about the accuracy of online information [ 10 , 11 , 12 , 13 ]. The COVID-19 pandemic has accelerated the flow of chronic illness information online, including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The infodemic has resulted in a lot of true, false, and mixed information on the Internet. Non-evidence-based, untrustworthy, erroneous, deceptive, or misleading data might make information acquisition more challenging [ 7 , 12 , 13 , 14 , 15 ]. The vast amount of cancer information available online can be overwhelming, confusing, and disturbing for some patients, especially if they are unable to filter and digest it [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, past research identified health concerns' (HC's) significance in predicting customers' behavioral responses regarding M-payment (Sreelakshmi and Prathap, 2020). The M-payment aspect also requires scrutiny in the context of management and psychology theories (Compeau and Higgins, 2017; Abu Daabes and Kharbat, 2019). However, few studies have investigated HC as driving elements of M-payment CI (Goel et al, 2021).…”
Section: Mobile Payment Service Quality 2019mentioning
confidence: 99%